Building Sociological Imagination through Social Media:: A Study on Instagram Account @Sociology_Perspective - Annissa Damayanti; Rakhmat Hidayat; Afdhal Afdhal (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2023)
This paper has three critical purposes. Firstly, to describe the content and activities presented by the @Sociology_Perspective Instagram account as an attempt to enrich our understanding of sociology. Secondly, to explain the shape of the Instagram account strategy for building sociological imagination. Thirdly, to illustrate the sociological analysis of learning sociology based on the Instagram platform using Wright C Mills' thinking about sociological imagining. A qualitative approach with case study methods was used for research, and data was collected through observations, in-depth interviews, and online documentation. The results of this paper show that the @Sociology_Perspective Instagram account has a variety of content and activities consisting of writing spaces, discussions, and information activities that improve sociological understanding, academic and soft skills, and critical thinking. In the context of sociology learning, such an increased capacity makes sociology a fascinating and easier-to-understand discipline with popular learning formats. The various content and activities on the @Sociology_Perspective Instagram platform are part of building sociological imagination that helps students link situations and social structures with their personal experiences. This process also trains and stimulates students to reflect on the social world with sociological concepts